∊-MSR Codes: Contacting Fewer Code Blocks for Exact Repair (conf) - Guruswami, Venkatesan; Lokam, Satya; Jayaraman, Sai Vikneshwar Mani (2018 IEEE International Symposium on Information Theory (ISIT), 2018)
ε-Minimum Storage Regenerating (ε -MSR) codes form a special class of Maximum Distance Separable (MDS) codes, providing mechanisms for exact regeneration of a single code block in their codewords by downloading slightly suboptimal amount of information from the remaining code blocks. The key advantage of these codes is a significantly lower sub-packetization that grows only logarithmically with the length of the code, while providing optimality in storage and error-correcting capacity. However, from an implementation point of view, these codes require each remaining code block to be available for the repair of any single code block. In this paper, we address this issue by constructing ε -MSR codes that can repair a failed code block by contacting a fewer number of available code blocks. When a code block fails, our repair procedure needs to contact a few compulsory code blocks and is free to choose any subset of a fixed size for the remaining choices (from the available code blocks). Further, our construction requires a field size linear in code length and ensures load balancing among the contacted code blocks in terms of information downloaded from them.